Efeito da neuromodulação na ilusão da mão de borracha - Dall'Agnol, Patricia Aparecida (2016)
The Rubber Hand Illusion (RHI) is generated by the conflict between synchronized visual and tactile stimuli delivered at the same time in the participant’s hand, occluded from the vision, and in a visible rubber prosthesis. Such conflict generates the sensation of incorporation of the extra limb in the participant. This illusion enable evaluate body awareness and how we perceive our body and single parts of it. Neuroimaging studies show that during the RHI the main cortical areas activated are the Premotor Cortex (PMC) and the Posterial Parietal Cortex (PPC). The knowledge of this areas playing an important role of multisensory integration that underlies the generation of the illusion and that the transcranial direct current stimulation (tDCS) technique has the ability of interfere on cortical activity, this study aimed to investigate possible neuromodulatory effects during the perception of the RHI. Specifically, we investigated effects of tDCS over PMC and PPC over i) time to perceive the RHI, ii) proprioceptive shift and iii) intensity of the illusion, measured via questionary. We evaluated 36 volunteers divided in 2 groups. The group 1 received tDCS over the PMC and the group 2 received tDCS over the PPC. The applied montages to both groups were: i anodal current at right hemisphere and cathodal current at left hemisphere; ii. anodal current at left hemisphere and cathodal current at right hemisphere; and iii. Sham condition.We verify that when tDCS was applied over the PMC using anodal current on the right hemisphere and cathodal current on the left hemisphere there is a significant effect on the proprioceptive shift task. Specifically, the volunteers had a greater shift towards the extra limb when compared to sham condition. However we found no effects for the opposite montage. Regarding the application of tDCS over PPC, we observed that the montage of anodal current on the right hemisphere and cathodal current on the left hemisphere promotes significant effects over the time taken to perceive the RHI. Specifically, this stimulation results in faster appropriation of the extra limb when compared to the opposite montage and to sham conditions. Finally, no effects of tDCS were found at the questionary evaluation in none of the groups. Thus, the study demonstrated that application of anodal right and cathodal left tDCS, in both of the studied areas promotes an increased perception of the RHI. In conclusion, this studiy increases the knowledge of the role of PMC and PPC in the integration of visual and tactile stimuli during the RHI, thus increasing knowledge about the aspects of body ownership. Besided it signals the possibility of tDCS as na useful tool for studies in this área and following from clinical application.